PENGARUH PENGAWASAN INTERN TERHADAP PENINGKATAN DISIPLIN KERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM BIDANG BINA MARGA - Juliahir Barata (Jurnal Ekonomi Integra, 2013)
In these papers, we investigate impact of internal control to discipline. We use causality research method to answer the problem. In this study we used 30 samples from 100 populations, and for sampling method we use purposive. From the analysis with linier regression, it’s found that intern control positively related to the work disciplines.